Diagnóstico y propuesta de mejoras de la planta de tratamiento de aguas residuales de la Municipalidad de La Unión, en la comunidad de Monserrat en Concepción, Cartago - Ortiz-Obando, Ariana Paola (Instituto Tecnológico de Costa Rica, 2016)
Urbanization causes a high impact on water resources due to the large volumes of contaminated water that must be treated. Wastewater treatment is a major challenge for Costa Rica, where coverage of sewerage with adequate treatment is only 4.2 %. In the community of Monserrat, in La Unión, Concepción, the Municipality is in charge of the treatment unit, which purifies the wastewater of approximately 813 homes. The plant consists of a Sequence Batch Reactor System (SBR), which has currently three aeration tanks and a drying bed for waste sludge treatment. Because of the presence of operational problems in the plant, such as foam in the reactors, and problems of overflow to the inlet capacity and the drying beds, a diagnosis was conducted in the system in order to identify opportunities for improvement at the levels of redesign, operation and maintenance. On this basis propose alternatives of action that would enable greater efficiency in the process. The diagnosis consisted of an initial phase of preliminary assessment of the system with the study of practices, physico-chemical, sizing and visual indicators considered essential in biological treatment processes. Once obtained the product of this phase the results were analyzed by comparing them with the theory in order to identify elements that can be corrected or improved and make the respective proposals. The diagnosis showed as the main problem the few or no purge of the excess sludge of the reactors, which triggers the overgrowth of filamentous microorganisms, high cellular retention times, low F/M relations and overconsumption of the available oxygen which generates low DO levels. Also a growth is denoted in the income flow of the plant of about 28.5 %, exceeding the maximum installed capacity of the handling units.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2016.
Keywords: Agua residual; Plantas de tratamiento; Lodos activados; Lechos de secado; Reactores de flujo discontinuo secuencial